Commercial Vehicles 2023: - VDI Wissensforum GmbH (VDI Verlag, 2023)
Content The Future of Transport European policy for future road vehicles – technological neutrality or ideological astray? 1 ANITA Integration autonomous trucks in an intermodal Hub – Starting the automatization of logistic hubs 13 Energy Infrastructure The future is Megawatt Charging – A high power revolution on charging infrastructure for commercial vehicles 25 Dynamic charging for trucks 35 Automated Driving Automated driving on Yards: Do we have to wait for fully autonomous vehicles to be ready for the market? 47 Megawatt-Charging Use Cases and technical challenges of the MCS charging 51 Megawatt charging as an enabler for battery-electric long-haul trucks – is that enough? 55 Digitalization AI-Supported Assessment of Load Safety 67 Fleet data used for self-learning functions in commercial vehicles 81 Virtual Type-IIa – Software product for homologation of commercial vehicle BEV without additional hardware 93 Pathways to Zero Emission How can hydrogen combustion engines contribute to realizing climate targets? 105 Fuel cell electric drive...